The study of the peasantry in the Peruvian social sciences: Advances, limitations and new perspectives - Walker, Charles (1989)
Peruvian intellectual life in recent decades has been characterized by a growing attention to the countryside. There are hundreds, perhaps thousands, of works from different perspectives and disciplines on the problem of the peasantry. A review of the magazines —always a good indicator of the Peruvian intellectual context— of recent years, demonstrates this interest: Allpanchis itself, Revista Andina, Sur, Indigenous Literature, Kamak Maqi and Agrarian Debate are some current examples.